Suitability of key Central American agroforestry species under future climates: an Atlas. - Sousa, K. de; Zonneveld, M. van; Imbach, Pablo; Casanoves, F.; Kindt, Roeland; Ordoñez, Jenny C. (2017)
This atlas provides habitat suitability maps for 54 species that are widely used in Central America for shade in coffee or cocoa agroforestry systems. The 54 species represent 24 fruit species, 24 timber species and 6 species used for soil fertility improvement. Suitability maps correspond to the baseline climate (1960-1990) and 2050 climates predicted for Representative Concentration Pathways (RCP) 4.5 and 8.5. Habitat was classified as suitable in future climates if a minimum of 12 out of 17 downscaled Global Circulation Models predicted suitable climates. Details of the methodology of ensemble suitability modelling with the BiodiversityR package are provided in the atlas.